The growing importance of economic relations between China and Latin America. The Peruvian case - Cornejo Ramírez, Enrique Javier (2021)
This article reviews the background of China’s trade relations with the world, the process of opening up from the seventies of the twentieth century and the profound changes that have been taking place in the first decades of the twenty-first century, with a “trade war” between the United States and China and with the progress that the Chinese economy and companies have been having in sectors such as energy and technology communications. The article also reviews the trade and economic relations between China and the countries of Latin America and the Caribbean, placing special emphasis on the case of Peru, where China is already the leading trading partner in both exports and imports. There is concern that the countries of the region are mainly exporting to China commodities such as minerals and food, which is why it is necessary to achieve a more equitable and value-added exchange.